ANTIDEPRESSANT ACTIVITY TEST OF RED BETEL LEAF ETHANOL EXTRACT (Piper crocatum) ON MALE WHITE MICE (Mus musculus) USING THE FORCED SWIM TEST METHOD - Triswanto Sentat; Anita Apriliana; Siti Lili Rizki Sari; Novi Milasari; Ghina Adhila; Rizki Rahmadi Pratama; M. Hasan Andryanto (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2025)
Red betel leaves (Piper crocatum) contain flavonoids, alkaloids, polyphenols, tannins, and which is known for its antidepressant properties. The purpose of this study was to determine the effect of antidepressant activity of ethanol extract of red betel leaves on male white mice (Mus musculus) orally. The method used in testing antidepressants is the Forced Swim Test. Fifteen mice were divided into five groups: a positive control group receiving 3.5 mg/kg BW amitriptyline, a negative control group, and three groups receiving 200, 400, and 800 mg/kg BW of the extract. The antidepressant effect was measured by observing the immobility of mice during swimming. The results of the study using paired sample t-Test analysis showed that there was a difference in immobility before and after, in the 400 mg/kg BW extract and 3.5 mg/kg BW amitriptyline dose groups had significant differences.